Effects of deep brain stimulation of the subthalamic nucleus on patients with Parkinson's disease: a machine-learning voice analysis - Suppa, Antonio; Asci, Francesco; Costantini, Giovanni; Bove, Francesco; Piano, Carla; Pistoia, Francesca; Cerroni, Rocco; Brusa, Livia; Cesarini, Valerio; Pietracupa, Sara; Modugno, Nicola; Zampogna, Alessandro; et al. (Frontiers in Neurology, 2023)
Introduction: Deep brain stimulation of the subthalamic nucleus (STN-DBS) can exert relevant effects on voice in patients with Parkinson’s disease (PD). We here examined voice objectively in STN-DBS patients with PD, by using artificial intelligence. Materials and Methods: In a cross-sectional study, we enrolled 108 controls and 101 patients with PD. The cohort of PD consisted of a first group of 50 patients with STN-DBS and a second group of 51 patients under the best medical treatment. Voice was clinically evaluated using the Unified Parkinson’s Disease Rating Scale part-III subitem for voice (UPDRS-III-v). We recorded and then analysed voices using specific machine-learning algorithms. The likelihood ratio (LR) was also calculated as an objective measure for clinical-instrumental correlations. Results: Clinically, voice impairment was greater in STN-DBS patients than in those under oral treatment. Machine-learning discriminated voices recorded from STN-DBS patients and those under oral treatments, objectively and with high accuracy. We also found significant clinical-instrumental correlations since the greater LRs, the higher UPDRS-III-v scores. Discussion: STN-DBS deteriorates speech in patients with PD as objectively demonstrated by machine-learning voice analysis.